Distribution of Interseismic Coupling Along the North and East Anatolian Faults Inferred From InSAR and GPS Data. Issue 16 (21st August 2020) - Bletery, Quentin; Cavalié, Olivier; Nocquet, Jean‐Mathieu; Ragon, Théa
Abstract: The North Anatolian Fault (NAF) has produced numerous major earthquakes. After decades of quiescence, the M w 6.8 Elazığ earthquake (24 January 2020) has recently reminded us that the East Anatolian Fault (EAF) is also capable of producing significant earthquakes. To better estimate the seismic hazard associated with these two faults, we jointly invert interferometric synthetic aperture radar (InSAR) and GPS data to image the spatial distribution of interseismic coupling along the eastern part of both the NAF and EAF. We perform the inversion in a Bayesian framework, enabling to estimate uncertainties on both long‐term relative plate motion and coupling. We find that coupling is high and deep (0–20 km) on the NAF and heterogeneous and superficial (0–5 km) on the EAF. Our model predicts that the Elazığ earthquake released between 200 and 250 years of accumulated moment, suggesting a bicentennial recurrence time. Plain Language Summary: Earthquakes are thought to occur on coupled fault portions, which are "locked" during the time separating two earthquakes, while tectonic plates are steadily moving. The spatial distribution of coupling has been imaged along numerous large faults in the world, but despite its considerable associated seismic hazard, not on the North Anatolian Fault (NAF). The recent M w 6.8 Elazığ earthquake (24 January 2020) has reminded us that the East Anatolian Fault (EAF) is also capable of producing large earthquakes. To better assess the seismic hazard associated with both the NAF and the EAF, we image the distribution of interseismic coupling along these faults. We find that the NAF is strongly coupled along most of the studied section. On the opposite, coupling is shallow and heterogeneous along the EAF. The initiation of the Elazığ earthquake coincides with a strongly locked but narrow (5 × 14 km) and superficial patch. The rest of the rupture extends over moderately coupled fault portions. We estimate that it took between 200 and 250 years to accumulate the moment released by the Elazığ event. Several fault segments along the EAF present similar coupling distributions, suggesting that, provided enough time, they could host earthquakes of similar magnitude. Key Points: Distribution of interseismic coupling on the North and East Anatolian Faults Bayesian quantification of uncertainties on coupling and Euler poles The 2020 M w 6.8 Elazig earthquake released 221.5 years (±26) of accumulated moment